Electrical Wiring Commercial, 17th Edition - Phil Simmons; Ray C. Mullin (Cengage Learning, 2020)
Completely revised and updated to reflect the 2020 National Electrical Code® (NEC®), ELECTRICAL WIRING COMMERCIAL, Seventeenth Edition, offers the most current coverage available. This reader-friendly, trusted resource is filled with vibrant, full-color illustrations and photographs, bringing even difficult concepts to life and making complex material easier to understand. In addition to updates based on the 2020 NEC, the Seventeenth Edition features information on important new developments in electrical design and installation, an increased emphasis on green technologies and safety in the workplace, providing ample coverage of topics you will likely encounter as a working professional in this dynamic field. Providing uniquely practical preparation for real-world success, the text includes a full set of blueprints that walk you through designing and installing an electrical installation compliant with the latest edition of the NEC.